2013
DOI: 10.1109/led.2013.2285305
|View full text |Cite
|
Sign up to set email alerts
|

InGaN Flip-Chip Light-Emitting Diodes With Embedded Air Voids as Light-Scattering Layer

Abstract: InGaN-based light-emitting diode (LED) with an embedded air-gap disks structure was fabricated through a laser drilling process and an electrochemical (EC) wet etching process. The disk-shaped air-gap structure was formed surrounding the laser-drilled hole as a light reflective structure to enhance the light extraction efficiency. The light output power of the treated LED structure had an approximate 22% enhancement when compared to a conventional LED at 20 mA.High light emission intensity of the treated LED s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…All the chip sizes used for the experiments were 1 × 1 mm 2 . 30) The roomtemperature current-voltage (I-V) characteristics of the LEDs were measured with an HP-4156C semiconductor parameter analyzer. The light output power-current (L-I) characteristics of the LEDs were measured with an integrated sphere associated with a current meter.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…All the chip sizes used for the experiments were 1 × 1 mm 2 . 30) The roomtemperature current-voltage (I-V) characteristics of the LEDs were measured with an HP-4156C semiconductor parameter analyzer. The light output power-current (L-I) characteristics of the LEDs were measured with an integrated sphere associated with a current meter.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Recently, Lai et al reported an ex situ AlN buffer layer deposited by sputter, which yielded an interruption-free GaN epitaxy [28]. To further improve the light extraction efficiency, Sheu et al implanted Ar into a sputtered AlN nucleation layer, and their results showed that the GaN-based epitaxial layer grown on implanted regions has lower growth rates than the implantation-free regions, which eventually form the embedded air voids [29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…However, conventional LEDs have a low light extraction efficiency in the central mesa region because of the large difference in refractive index between the GaN (2.5) and the air (1.0). Photonic crystal structures, 2) a nanorod structure, 3) a photoelectrochemically treated microhole-array pattern, 4) embedded air protrusions, 5) laser-induced periodic structures, 6) air void structures, 7) conical air prism arrays, 8) embedded air voids/SiO 2 nanomasks, 9) embedded air voids grown on selective-area Ar-implanted sapphire, 10) laserinduced dumbbell-like air-voids, 11) and an air-gap embedding GaN template 12) have all been used to increase the light extraction efficiency of InGaN-based LEDs on Al 2 O 3 substrates. The doping selective etching technique for heavily doped GaN:Si layers has been reported for the chemical lift-off process in InGaN LED structures.…”
mentioning
confidence: 99%